When the rehearsals stop: the reality of music making after high school orchestra - Bishop, Jeffrey Scott (Kansas State University, 2015)
The purpose of this study was to discover the reasons that led high-achieving high school orchestra musicians to discontinue formal participation in collegiate orchestra class. Using narrative analysis, the researcher examined the intrinsic and extrinsic factors that influenced the student’s decision to not participate in orchestra. The researcher also sought to understand if and how these former high school musicians continued to make music on their own. Three current university students and their high school orchestra teachers were purposefully selected for the study. Data were collected through email queries, surveys, and personal interviews. Upon completion of the interview, the researcher summarized each interview into a narrative and shared it with the participant via email for member checking. Each participant was asked to provide feedback for the narrative and return it to the researcher. The researcher used Riessman’s (2008) adaptation of William Labov’s structural coding to analyze the data. Using Robichaux’s (2003) expansion of Labov’s coding, the researcher was able to establish a structural analysis of the narrative that reinforced the thematic analysis. The researcher coded each participant’s narrative along with that of his or her high school orchestra teacher. Coding was supported by NVivo software. Fact-checking of responses from the initial survey along with answers from the participants’ narrative and that of their high school director’s narrative allowed for a more robust and reliable narrative analysis. Definitive answers were not be sought or expected, but rather the collection of data led to a greater understanding and illustration of why the research participants chose to end their participation in orchestra rehearsals on the collegiate level. The participants offered diverse reasons for why they chose not to continue participating in college on the university level. Their reasons are described within six categories of intrinsic and extrinsic factors: (a) persistence; (b) self-concept of musical ability; (c) motivation for music; (d) parental musicianship and support; (e) director influence; and (f) socioeconomic status. Each participant could not name a single, defining factor that led him or her to discontinue participation in orchestra as each of the identified factors weighed differently for each person.
Keywords: Orchestra attrition; Music Education (0522)